2021
DOI: 10.1038/s41467-021-24519-5
|View full text |Cite
|
Sign up to set email alerts
|

Higher socioeconomic status does not predict decreased prosocial behavior in a field experiment

Abstract: Does higher socioeconomic status predict decreased prosocial behavior? Methodological issues such as the reliance of survey studies on self-reported measures of prosociality, the insufficient control of relative incentives in experiments, and the use of non-random samples, have prevented researchers from ruling out that there is a negative association between socioeconomic status (SES) and prosociality. Here, we present results from a field experiment on the willingness of unaware individuals of different SES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 56 publications
4
46
1
3
Order By: Relevance
“…We found a moderating effect of unequal economic rank on the relationship between objective status and altruism, but contrary to what could be expected from previous studies (Côté et al, 2015;Piff & Robinson, 2017), our results showed that higher objective status participants were, on average, more altruistic when they enjoyed higher economic status -but we did not find this moderating effect when considering the subjective status participants. Thus, our results align with what has been documented in more recent studies (Hermanni & Tutić, 2019) and corroborate experimental research that has found similar results in both WEIRD (Andreoni et al, 2021;Clerke et al, 2018) and non-WEIRD (Salgado et al, 2019) samples: those who have less are not more altruist than those who have more. Cultural factors could explain why higher objective-SES individuals behave more altruistically when enjoying a slight economic advantage.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found a moderating effect of unequal economic rank on the relationship between objective status and altruism, but contrary to what could be expected from previous studies (Côté et al, 2015;Piff & Robinson, 2017), our results showed that higher objective status participants were, on average, more altruistic when they enjoyed higher economic status -but we did not find this moderating effect when considering the subjective status participants. Thus, our results align with what has been documented in more recent studies (Hermanni & Tutić, 2019) and corroborate experimental research that has found similar results in both WEIRD (Andreoni et al, 2021;Clerke et al, 2018) and non-WEIRD (Salgado et al, 2019) samples: those who have less are not more altruist than those who have more. Cultural factors could explain why higher objective-SES individuals behave more altruistically when enjoying a slight economic advantage.…”
Section: Discussionsupporting
confidence: 93%
“…Recent research has cast doubts on the negative relationship between social status and prosociality, with some studies concluding that there is no clear link (Dubois et al, 2015;Trautmann et al, 2013) or even a positive relationship between the two (Andreoni et al, 2021;Bauer et al, 2014;Korndörfer et al, 2015;Tutić & Liebe, 2020). Due to these conflicting results, some researchers have proposed that inequality moderates the association between social status and prosociality (Piff & Robinson, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Prosocial behavior refers to the actions undertaken to benefit other people (Yang et al, 2021). While initial researches demonstrated a negative relation between SES and prosocial behaviors, subsequent studies did not corroborate these findings (Andreoni et al, 2021;Trautmann et al, 2013). In a similar vein, several works suggested null relation between SES and prosociality (Côté et al, 2015;Dubois et al, 2015).…”
Section: The Impact Of Socioeconomic Status On Prosocial Behaviormentioning
confidence: 99%
“…Numerous empirical studies also support this result. For example, Andreoni, Nikiforakis, and Stoop [ 14 ] found that the poor were less likely to return misdelivered envelopes, even if it was not good for them to keep them. A series of studies conducted by Korndörfer et al [ 13 ] also found that people with lower status spent a lower percentage of their income on philanthropy and were less likely to make charitable donations than those with higher status.…”
Section: Introductionmentioning
confidence: 99%